Audit Quality Research: A Bibliometric Study of Global Trends and Emerging Themes - Sulistyo, Sulistyo; Fauzan, Fauzan; Sahlan, Mohd Khairulnizam (Accounting Study Program, Faculty Economics and Business, Universitas Sebelas Maret, 2025)
In recent years, scientific audit quality output has increased. However, there is still a scarcity of research that provides a comprehensive picture of the situation. This research aims to spot trends in audit quality research and scientific production, such as sources, authors, and documents, across time. A total of 1356 papers published between 1968 and 2024 were analyzed using bibliometric analysis. Audit quality is a query used in article titles to get metadata from the Scopus bibliographic database. The analysis was built using biblioMagika for frequency analysis, VOSviewer for data visualization, and Harzing's Publish or Perish for citation metrics and research. The findings reveal an increase in audit quality literature from 1968 to 2024, with a notable increase since 2013. Various studies on audit quality incorporating multi-author collaboration have been published in various languages, with 160 writers from 104 countries and 160 organizations. The United States, the United Kingdom, Australia, China, and Indonesia were the top contributors to this study, and these data may aid future research into the global overview of audit quality studies over time.